Kursus Penjamah Makanan pada Jasa Boga PT “X” di Madiun - Ratih Lukmitarani; Muryoto Muryoto; Rizki Amalia (Poltekkes Kemenkes Yogyakarta, 2018)
Poor habits of food handlers are primary and secondary source of pathogens or toxigenic micro-organisms which are ready to be infected through food, either via direct or indirect contactwhich is causing enteric diseases among humans. Food borne diseases can be prevented bygiving education to food handlers as suggested by the regulation issued by MoH No.1096/Menkes/Per/VI/2011 about Hygiene Sanitation for Catering Service, which is known as FoodHygiene and Sanitation Course. This course is conducted by two methods, i.e. through lectureand tutorial. The aim of the study was to identify the difference about knowledge mastering between pre-couse and post-course, among the food handlers of PT “X” Catering Service in Madiun. The study was a true experiment with pre-test post-test control group design. From 55food handlers as the study population, 32 were randomly selected as the sample, of which 16were assigned to lecture group and the other 16 to tutorial one. The data were analyzed by ttest, and the results show that the knowledge receiveness about food hygiene and sanitationamong the food handlers between pre-course and post-course is significantly different, either inthe lecture group (p-value<0,001) or in the tutorial group (p-value<0,001). The mastering ofcourse material through tutorial method increased higher (17,3 %), compared with that of lecture method which was only 17,3 %. To conclude, the mastering of course material betweenpre-course and post-course is different, either through lecture method or tutorial method.